2021
DOI: 10.1183/13993003.02463-2020
|View full text |Cite|
|
Sign up to set email alerts
|

Mendelian randomisation and experimental medicine approaches to interleukin-6 as a drug target in pulmonary arterial hypertension

Abstract: Inflammation and dysregulated immunity are important in the development of pulmonary arterial hypertension. Compelling preclinical data supports the therapeutic blockade of interleukin-6 signalling.We conducted an open-label phase-II study of intravenous tocilizumab (8 mg·kg−1) over 6 months in group 1 pulmonary arterial hypertension. Co-primary endpoints were safety, defined by incidence and severity of adverse events, and change in pulmonary vascular resistance. Separately, a Mendelian randomisation study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…It is noteworthy that the drug was given one week after MCT injection to Wister rats, a week earlier than given in our study, which might increase its opportunity to improve PAH by preventing (rather than regressing) adverse pulmonary vascular remodeling. Toshner et al reported that tocilizumab (an IL-6 specific antibody) did not significantly alter PAH severity in human PAH 48 .…”
Section: Important Markers Of Rv Dysfunction (Anp) and Fibrosis (Tota...mentioning
confidence: 99%
“…It is noteworthy that the drug was given one week after MCT injection to Wister rats, a week earlier than given in our study, which might increase its opportunity to improve PAH by preventing (rather than regressing) adverse pulmonary vascular remodeling. Toshner et al reported that tocilizumab (an IL-6 specific antibody) did not significantly alter PAH severity in human PAH 48 .…”
Section: Important Markers Of Rv Dysfunction (Anp) and Fibrosis (Tota...mentioning
confidence: 99%
“…In SSc, the paradigm vasculopathic disease for PAH, IL-6 serum levels were also increased when compared to healthy controls and correlated with disease severity ( 78 ). Nevertheless, due to the exclusion criteria, the major etiology of CTD-aPAH in the study of Toshner et al was SSc ( 70 ). This study showed that more patients with CTD-aPAH had a >15% reduction in PVR after 6 months of tocilizumab treatment, in comparison to IPAH/HPAH patients.…”
Section: Clinical Implementation Of Immune Suppression In Pahmentioning
confidence: 98%
“…This makes IL-6 an interesting potential therapeutic target. The use of tocilizumab (anti-IL-6-receptor blocker) has been investigated for itsefficacy in PAH, in a randomized phase 2 clinical trial ( www.clinicaltrials.gov NCT02676947) ( 69 , 70 ). Six months of treatment with tocilizumab, in this selection of patients, showed no significant improvement of PVR.…”
Section: Clinical Implementation Of Immune Suppression In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential improvement was noted in the small subgroup of patients with CTD-associated PAH. This raises the possibility that disease is driven by inflammation in only a subset of patients [47]. Other cytokines represent relevant therapeutic targets like tumour necrosis factor (TNF).…”
Section: Targeting Inflammation and And Dysregulated Immunity In Pahmentioning
confidence: 99%